IMPACT OF COVID-19 ON PHYSICAL ACTIVITY OF HIGH SCHOOL STUDENTS (BULGARIAN EXPERIENCE) - B. Zlatev; D. Ilieva (Trakia Journal of Sciences)
The neglect of physical activity in the education of high-school students (14 – 19 years old) during the COVID-19 pandemic could lead to serious consequences for their physical development and put their health at risk. In order to mitigate the problem with inactivity many countries all over the world use different approaches to sports classes. In cases where attendance is not possible, it is necessary to provide distance learning with maximum efficiency. The aim of the study was to examine the opinion of high-school students on the influence of COVID-19 on their physical activity and to optimize the learning process in physical education and sports under the conditions of distance learning in an electronic environment (DLEE). The study was carried out with 43 respondents who met the criteria of the target group. The survey was administered in two phases. Two questionnaires were completed by the participating students. The analysis of the results shows that in Bulgaria the pandemic does not have a negative influence on the physical activity of high-school students. We assume that the main reasons for this observation are the more liberal measures and the availability of options to use different sports facilities. In perspective, it would be useful to identify contemporary and innovative methods for improvement and monitoring of the activity of high-school students under the conditions of DLEE.